In silico Identification of a Molecular Circadian System With Novel Features in the Crustacean Model Organism Parhyale hawaiensis - Hunt, Benjamin James; Mallon, Eamonn B.; Rosato, Ezio (Frontiers in Physiology, 2019)
The amphipod Parhyale hawaiensis is a model organism of growing importance in the fields of evolu- tionary development and regeneration. A small, hardy marine crustacean that breeds year-round with a short generation time, it has simple lab culture requirements and an extensive molecular toolkit includ- ing the ability to generate targeted genetic mutant lines. Here we identify canonical core and regulatory clock genes using genomic and transcriptomic resources as a first step in establishing this species as a model in the field of chronobiology. The molecular clock of P. hawaiensis lacks orthologs of the canonical circadian genes cryptochrome 1 and timeless, in common with the mammalian system but in contrast to many arthropods including Drosophila melanogaster. Furthermore the predicted CLOCK peptide is atypical and CRY2 shows an extended 5’ region of unknown function. These results appear to be shared by two other amphipod species.